BELLA’S INFLUENCE: TWILIGHT AND INDONESIAN YOUNG ADULT NOVELS - Tri Pramesti (Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract. This paper discusses the influence of Stephanie Meyer’s Twilight in Indonesian young adult novels. Tuilet and E’pliss are full of references to Meyer’s Twilight , both direct and indirect, in names of characters such as Edward Cullen and Bella and theme which take the inspiration from Twilight. By using Roland Barthes’s theory of intertextuality and Reference Code and Bloom’s literary influence, this paper is expected to provide a critical analysis of how Twilight influences Indonesian young adult fictions. Through cultural texts written for young readers, it will also be seen how cultural background of the author influence the writing. By applying heuristic and hermeneutics methods in literary reading this study identifythe moral message of the author and how the process of understanding of the author worked. As stated by Roland Barthes that there is no original text for each text is affected by various writings, place and time, it will be seen how far the influence of the novel Twilight on Indonesian contemporary young adult fictions. Keywords: Cultural Code, intertextuality, Indonesia young adult fiction, Literary Influence